Análise da fase de implementação da Política Estadual de Promoção da Saúde (POEPS) nos municípios de Minas Gerais. - Conceição Aparecida Moreira (2020)
The State Health Promotion Policy (SHPP) was implemented inBrazil in an unprecedented way, by means of the “SES/MG nº 5250” Resolution of April 19 of 2016, with the goal of highlighting, valueing and encouraging the development of health promotion actions in the cities of Minas Gerais state. That is arecently implanted policy in the state, and it is relevant to analyse its implementation period in the cities. The guidelines are structure, processes and involving results. The study purpose was to assess the SHPP period in all cities inside the state which joined the policy, aiming at subsidizing state management for reorganization of the actions implementation, with a view to the enhancement of health promotion at SUS (that is, the Unified Health System). This is an observational, transversal, descriptive study, carried out with the qualitative method. As for data collecting, a structured, self-applied online questionnaire was used, which approached structure and process variables. For that purpose, it used secondary data belonging to the Management System of State Health Resolutions (MSSHR). The study population included 852 cities which joined SHPP in 2016. The sample was probabillistic, simple, done at random, and it was made of 360 cities proportionately distributed among 28 regional health units,taking into account populational size. For implementation degree, the analysis and judgement matrix was used, where sub-dimensions set for this study were scored. The scores that were used to assess implementation degree were defined as: critical implementation for values between 0 and 49.9%; partial implementation between 50.0% and 79.9%; and acceptable implementation when above 80.0%. In addition, SHPP logical model and the analysis and judgement matrix were prepared. Among the results found, it was possibleto verify that SHPP is partially implemented (65.0%) in the set of cities within the state. All dimensions showed partial implementation, both for cities set and population size, except for sizes of processes showing critical application in medium-sized cities. Also,some weaknesses were indicated: input sub-dimension, which presented critical implementation in medium and large-sized cities; sub-dimension of process management with critical implementation for the state as a whole and for all populationgroups, as wellas information management sub-dimension exhibiting critical implementation in medium-sized cities. As potentialities, a sub-dimension of administrative management was identified, which presented acceptable implementation for the state as awhole, and for both small-sized cities I and II and the large-sized ones. Results revealed low institutionalization of health promotion actions in Minas Gerais’ cities, as well as a need for measures to be applied by managers, aiming to change this reality through investments in planning, organization, training, management, operationalization, monitoring, evaluation and execution of actions, converging on improving actions implementation, and providing quality services and actions for the population. As a dissertation product, it was also delivered to the State Department of Health (SES/MG) through a technical report.